Mixture Preparation in a Four-Stroke Compression Ignition Engine – A CFD Approach - Kalivarathan, G.; Jaiganesh, V. (Asian Review of Mechanical Engineering, 2012)
A CFD simulation is carried out to predict the effects of piston crown on the fluid flow field, inside the combustion chamber, cylinder of four strokes CI engine. The complete analysis is concentrated on the study of effects of the piston shape. On the fluid flow characteristics, fluid flow dynamics exhibits an important role on charge preparation to attain the better combustion performance and efficiency in the viscosity of swirl and tumble flows as turbulence. The turbulence parameters like swirl and tumble represents the fluid flow behavior occurs inside the combustion chamber, which influence the air streams to the cylinder during intake stroke and reasonably enhances the mixing of air and fuel to have a better mixing during compression stroke. The numerical calculations are preferred in a single cylinder four stroke diesel engine running at full throttle condition by using the CFD mode. Different Bowls are considered with an engine speed of 2200 rpm, for this analysis, to be compared to evaluate the swirl and tumble flows produced during intake and compression stroke. The results obtained from the numerical analysis can be used to predict uniformity in the structure of a charge for a efficient performance and combustion in a compression ignition engine.